Perbandingan dua jenis olahraga pada pagi dan malam hari terhadap kualitas tidur - Andriana, Laily Mita; Ashadi, Kunjung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
Basically, humans are through two phases in their lives, namely the ergotropic phase in which humans were active in the morning and the trophotropic phase in which humans do recovery at night. This study aimed to compare the two types of exercise carried out in the morning and at night to the quality of sleep. The research method used was quantitative descriptive approach with a treatment of one shot case study design by using 40 male students as subjects divided into four groups. To find out the difference in the quality of sleep during morning and night sessions, this study used t-test samples independent test. Based on the results of this study, it was shown that sleep quality of the group carrying out moderate-intensity continuous cycling activities in the morning and night sessions had P> 0.05 and the sleep quality of the group carrying out High Intensity Interval Training (HIIT) cycling in the morning and night session had a value of P <0.05. The conclusion of this study was that there was no significant difference in sleep quality between the groups carrying out moderate cycling activities in the morning and night session had a value of P <0.05. The conclusion of this study was that there was no significant difference in sleep quality between the groups carrying out moderate cycling activities in the morning and night, but there were significant differences in the quality of sleep between the groups carrying out HIIT cycling activities in the morning and night.